COVID-19 and global value chains: A discussion of arguments on value chain organization and the role of the WTO - Marc Bacchetta; Eddy Bekkers; Roberta Piermartini; Stela Rubinova; Victor Stolzenburg; Ankai Xu (World Trade Organization (WTO), 2021)
Since the outbreak of the COVID-19 pandemic there has been a discussion among researchers and policy makers about changes to global value chains, both about expected changes and changes that should be promoted by government policies. In this paper we conduct an in-depth analysis of the reasons for changes in global value chains as a result of COVID-19 both from a positive angle, analysing expected changes in the behaviour of firms, and from a normative angle, assessing the different arguments for policy interventions by governments. After this analysis international cooperation of trade policies and the role of WTO in crises like the COVID -19 pandemic is explored. The analysis generates three main conclusions. First, the COVID-19 pandemic could contribute to diversification of sources of supply whose extent will vary by sector depending on the costs of value chain reorganization. The pandemic, by contrast, is not likely to contribute much to re-shoring, the return of manufacturing activities to industrialized countries, which is more likely to be driven by pre-existing trends such as rising factor costs in emerging countries, increasing uncertainty about trade policy, and robotization and automation of production. Second, the pandemic has led to increased attention to the provision of essential goods in situations of crisis and our analysis concludes that to achieve this objective, global cooperation should be preferred to national policies such as domestic production and export restrictions. Third, the largest risk for the global economy in the aftermath of the pandemic is a move away from open, non-discriminatory trade policies, which would jeopardize the large benefits of open trade regimes in the current global economy characterized by scale economies, innovation spillovers, and a global division of labour.
Keywords: F1; 330; COVID-19; global value chains; provision of essential goods; export restrictions